THE NEED FOR THE RIGHT TO POSSESS AND FIRE FIREARMS IN INDIA - G, Tarun.; K, Roja. (International Journal of Psychosocial Rehabilitation, 2020)
The right to possess and bear firearms is recognised extent of an individual right to self defence in dire situations where such action is deemed necessary for the survival of the person inflicted. Legislations around the world have regulated and maintained the procedure of issue of license to possess and the permits to carry such ranged weapon with the individual. The issue with the right to possess and firearms is with the lack of proper framework backing up the process of issue of license and permits. Such as right is given to the people only for it to be used in times of personal defence. People have been using such weapons for their personal vendetta, using it to commit homicide, armed robbery, armed mugging and been shootouts in public, putting the general public in the threat of their lives. In several nations people with terrorism agenda have been using weapons to masscare people while putting forth their ideas of public cleansing and even in abetment of one’s suicide. For such reasons, anti-gun help groups have been pushing back the right to possess such firearm. For the effective regulation of gun violence control and effective gun usage. India has stricter gun control laws in comparison with several other nations, an ordinary citizen is prohibited from carrying a concealed weapon. Such a legislation perhaps projects the societal view on possession of gun as a fundamental need as weapon isn’t the one that ends up killing another, its the person behind the trigger